Description of Gastric Acidity (pH) with Simple Method in Lipopolysaccharide Induced Mice - Veterini, Anna Surgean; Wahjuprajitno, Bambang; Rehatta, Nancy Margarita; Rachmawati, Heni; Soedarmo, Subijanto Marto; Sudiana, I Ketut; P, Widodo Jatim; Adi, Annis Catur; Suhanda, Rachmad; Sarmanu, Sarmanu; Widjiati, Widjiati (Jurnal Veteriner, 2023)
The gastrointestinal acidity/pH can considerably influence the stability and absorption of oral medications. As a result, understanding the circumstances for drug delivery requires knowledge of gastrointestinal pH. Mice injected with lipopolysaccharide (LPS) are used in the most well-studied animal models of sepsis. However, information on gastrointestinal pH in sepsis mice is still insufficient. This study was conducted to identify gastric pH values in mice induced by lipopolysaccharide. The LPS was injected intraperitoneally as well as 0.9% NaCl as control groups. Treated groups (LPS) consisted of four groups and the control group (0.9% NaCl) consisted of four groups. Ten mice were used in each group. Gastric pH measurement was conducted using pH meter Lutron PH-201. Based on this study, the factors that influenced gastric pH in sepsis animal models were the LPS doses and the time after LPS injection. The results of gastric pH measurement in sepsis mice did not show a decrease in the pH compared to the normal conditions. The dose of LPS significantly influences the gastric pH change.